A Study of Histopathological Features Associated with Papillary Thyroid Carcinoma - Ridha Dirwal, Ameer; Mahdi Mohammed, Anfal; Muhsin Leaj, Duha; Mansour Jassim, Adnan; Mahmod Murad, Hawrra; Mohan Mohammed, Asaad; Hamza Maktuf, Ali (International Journal of Psychosocial Rehabilitation, 2020)
Histopathological Papillary thyroid carcinoma diagnosis is based on the main criteria, which are mostly detected by the pathologist. Therefore, the aim of our study is to provide information focused on this criterion Features. The percentage of patients with cancer of thyroid gland for last three years (2017, 2018, and 2019) was and The histopathological section of the thyroid tissue that is affected by papillary thyroid carcinoma is the hypochromic nuclei, occurrence of ground glass, as the prominent pattern associated with papillae of the tumor, the true infiltration of the venous vessels and psammoma bodies, the cells of tumor infiltration surrounding the parenchyma, tumor cells containing enlarged, overlapping nuclei, high proliferation with irregular counters with enlargement, fine chromatin, thyroid carcinoma characterized by papillary architecture with fibrovascular cores and high proliferation cells characterized by a papillary growth pattern, where the stroma is represented by conjunctiva - vascular fine septa Intranuclear cytoplasmic inclusions with high proliferation cells Ground glass nuclei. Conclusions: the histopathological features of the papillary thyroid carcinoma depend on the shape of nuclei and psammoma bodies with high proliferation cells.